2020 55th International Universities Power Engineering Conference (UPEC) 2020
DOI: 10.1109/upec49904.2020.9209759
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lithium-ion Battery Cells Degradation Based on Different Manufacturers

Abstract: Lithium-ion batteries are recognised as a key technology to power electric vehicles and integrate gridconnected renewable energy resources. The economic viability of these applications is affected by the battery degradation during its lifetime. This study presents an extensive experimental degradation data for lithium-ion battery cells from three different manufactures (Sony, BYD and Samsung). The Sony and BYD cells are of LFP chemistry while the Samsung cell is of NMC. The capacity fade and resistance increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Its duplicate cell C01 was more stable, demonstrating the more regularly observed early-life decrease and late-life increase in DCIR. An initial decrease in DCIR has also been reported by Gailani et al [5] but is otherwise seldom reported in literature. The phenomenon could be related to several possible causes, of which one could be variations in the formation process between cell candidates [17].…”
Section: B Correlation Between Direct Current Internal Resistance (Dc...supporting
confidence: 63%
See 1 more Smart Citation
“…Its duplicate cell C01 was more stable, demonstrating the more regularly observed early-life decrease and late-life increase in DCIR. An initial decrease in DCIR has also been reported by Gailani et al [5] but is otherwise seldom reported in literature. The phenomenon could be related to several possible causes, of which one could be variations in the formation process between cell candidates [17].…”
Section: B Correlation Between Direct Current Internal Resistance (Dc...supporting
confidence: 63%
“…All cycled cells also showed swelling at end of testing, especially cells cycled at high charge C-rates. Compared to cell tests done at similar test conditions presented in literature, the cycle life at 1C show higher values in our case for cell types B and C but generally lower values for cell type A [5], [7], [8]. In addition, for cell type C, a time-dependent ageing mechanism was also measured by means of a calendar ageing test at 50 % SOC.…”
Section: A Capacity Retention and Coulombic Efficiencysupporting
confidence: 58%
“…High temperatures and state of charge are critical factors contributing to the rapid decline in battery efficiency and capacity, and understanding these processes is key to developing strategies for their effective repurposing and utilization [10][11][12][13]. Accurate diagnostic and prognostic models for secondary energy storage systems are essential to maximize the performance and lifespan of repurposed EV batteries [14][15][16]. These models must account for factors such as calendar aging and cyclic aging, which significantly impact battery degradation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Tesla has claimed to develop a newer variant of the Lithium-ion battery that can back up the EV for around 300 miles in a run [13]. Samsung's Lithium-ion battery with 20 min charging cycle runs EV up to 375 miles [14,15]. Government agencies such as the US Department of Energy have dispatched measures to initiate charging ports and stations near the large EV parking spaces [16].…”
Section: Introductionmentioning
confidence: 99%